The Effect of Tin Addition to ZnO Nanosheet Thin Films for Ethanol and Isopropyl Alcohol Sensor Applications - Yuliarto, Brian; Julia, Sri; Wulan S., Ni Luh; Iqbal, Muhammad; Ramadhani, Muhammad F.; Nugraha, N. (Journal of Engineering and Technological Sciences, 2015)
The requirements of green environmental and public health monitoring have become stricter along with greater world attention for global warming. The most common pollutants in the environment that need tightened control are volatile organic compounds (VOC). Compared to other kinds of sensors, semiconductor sensors have certain advantages,  including high sensitivity, fast response, simplicity, high reliability and low cost. In this work, ZnO and Sn-doped ZnO nanostructure materials with high surface nanosheet areas were synthesized using chemical bath deposition. The X-ray diffraction patterns  could be indexed  according to  crystallinity  mainly to a hexagonal wurzite ZnO structure. The scanning electron microscopy (SEM) results showed that in all samples, the thin films after the addition of Sn consisted of many kinds of microstructure patterns on a nanoscale, with various sheet shapes. The sensor performance characterizations showed that VOC levels as low as 3 vol% of isopropyl alcohol (IPA) and ethanol could be detected at sensitivities of 83.86% and 85.57%, respectively. The highest sensitivity of all sensors was found at an Sn doping of 1.4 at%. This high sensor sensitivity is a result of the high surface area and Sn doping, which in turn produced a higher absorption of the targeted gas.